Domestic and international trials, 1700-2000: The trial in history, vol. II - Melikan, R. A. (Manchester University Press, 2003)
How does the trial function? What are the tools, in terms of legal principle, scientific knowledge, social norms, and political practice, which underpin this most important decision-making process? This collection of nine essays by an international group of scholars explores these crucial questions. Focusing both on English criminal, military, and parliamentary trials, and upon national and international trials for war crimes, this book illuminates the diverse forces that have shaped trials during the modern era. The contributors approach their subject from a variety of perspectives - legal history, social history, political history, sociology, and international law. With an appreciation and understanding of the relevant legal procedures, they address wider issues of psychology, gender, bureaucracy, and international relations within the adjudicative setting. Their inter-disciplinary approach imparts to this book a breadth not usually seen in studies of the courtroom. Scholars and students of modern British history, political science, and international law, as well as legal history, will find these essays stimulating and informative. Judicial tribunals in England and Europe, 1200-1700: The trial in history, vol. I, edited by Dr Maureen Mulholland and Professor Brian Pullan, is also published by Manchester University Press.